Revenue Collectors Competency on Achievement of Own Source Revenue in Kenyan County Governments (International Journal of Scientific Research and Management (IJSRM), 2024)
An alarming trend has emerged from an analysis of own source revenue as a percentage of the targeted annual revenue over the past five financial years, revealing a consistent decline in performance with counties raising less than 40% of their estimated own source revenue potential despite using agents and having undertaken automation of the revenue collection processes. A deeper examination further reveals that a significant number of counties that consistently outperform the national average in achieving own source revenue targets have already embraced automation, in addition to agency revenue collection. A mixed research design was adopted by this study, targeting a population of 708 employees working in six selected county governments. By use of the Yamane formula, the determined sample was 280, who were reached through both census and stratified random sampling technique. Primary was collected through structured questionnaires. In order to examine quantitative data, descriptive statistics such as frequency, mean, and standard deviation were used. The study findings reveal that there was an overall mean of 4.321 and a relatively low standard deviation of 0.823. This underscores the significance of skilled and competent revenue collection employees in achieving own source revenue targets. This finding has profound implications for county governments, emphasizing the critical need to invest in the training, development, and ongoing support of revenue collection personnel.